DNS Tunneling: a Review on Features - Sammour, Mahmoud; Hussin, Burairah; Othman, Mohd Fairuz Iskandar; Doheir, Mohamed; AlShaikhdeeb, Basel; Saad Talib, Mohammed (International Journal of Engineering and Technology, 2018)
One of the significant threats that faces the web nowadays is the DNS tunneling which is an attack that exploit the domain name protocol in order to bypass security gateways. This would lead to lose critical information which is a disastrous situation for many organizations. Recently, researchers have pay more attention in the machine learning techniques regarding the process of DNS tunneling. Machine learning is significantly impacted by the utilized features. However, the lack of benchmarking standard dataset for DNS tunneling, researchers have captured the features of DNS tunneling using different techniques. This paper aims to present a review on the features used for the DNS tunneling.Â